Investment decisions of public and private manufacturing firms in India - A, Malavika; Jain, Bhawana; Krishnan A. V, Hari (International Journal of Engineering and Technology, 2018)
The study intents to explore the factors that influence the investment decisions of public limited and private limited manufacturing firms in India. The data for the study was collected for a period of 10 years from CMIE Prowess. Variables such as ROA, Debt/Equity, Dividend and Total Expenditure have been considered as independent variables for the research. The study found that investment decisions of private firms are influenced by factors like ROA, Debt/Equity and Expenses, whereas the public firmsâ€™ investment decisions are influenced by ROA, dividend and Expenses.Â Â